One year failure rates for de-novo ventriculo-peritoneal shunts in under 3-month-old children. (4th May 2019) - Ved, R.; Bentley, E.; Amato-Watkins, A.; Lang, J.; Zilani, G.; Bhatti, I.; Leach, P.
Abstract: Introduction: Ventriculo-peritoneal shunts (VPS) are still the mainstay treatment for hydrocephalus in children. It is generally accepted that VPS failure and infection rates are higher for neonates than for older children. We compared our 1-year failure and infection rates in under 3-month-old children compared with older children in our department. Results: We identified 58 children under 3 months of age who underwent VPS insertion between January 2007 and December 2016. They had a 29.3% (17) shunt failure rate over the first year. There were two confirmed shunt infections (3.4%). Discussion: The 1-year shunt failure rate at our institution for VPS insertion in children over 3 months is 26.1% and the infection rate is 4.3% (9). The literature suggests that the outcome for VPS in younger children is worse than for older children. Our work shows similar outcomes for all children compared to those under 3 months at time of VPS insertion alone. Conclusion: Children under 3-months-old undergoing VPS insertion should not automatically expect an increased 1-year failure or infection rate compared with older children. The reasons for this may be as a result of increased subspecialisation, the more widespread use of antibiotic-impregnated catheters and improved neonatal care.